Evaluation of a new medical retrieval and primary health care advice model in Central Australia: Results of pre‐ and post‐implementation surveys. (9th December 2022) - Green, Danielle; Russell, Deborah Jane; Zhao, Yuejen; Mathew, Supriya; Fitts, Michelle Susannah; Johnson, Richard; Reeve, David Mark; Honan, Bridget; Niclasen, Petra; Liddle, Zania; Maguire, Graeme; Remond, Marc; et al.
Abstract: Introduction: In February 2018 the Remote Medical Practitioner (RMP)‐led telehealth model for providing both primary care advice and aeromedical retrievals in Central Australia was replaced by the Medical Retrieval and Consultation Centre (MRaCC) and Remote Outreach Consultation Centre (ROCC). In this new model, specialists with advanced critical care skills provide telehealth consultations for emergencies 24/7 and afterhours primary care advice (MRaCC) while RMPs (general practitioners) provide primary care telehealth advice in business hours via the separate ROCC. Objective: To evaluate changes in clinicians' perceptions of efficiency and timeliness of the new (MRaCC) and (ROCC) model in Central Australia. Design: There were 103 and 72 respondents, respectively, to pre‐ and post‐implementation surveys of remote clinicians and specialist staff. Findings: Both emergency and primary care aspects of telehealth support were perceived as being significantly more timely and efficient under the newly introduced MRaCC/ROCC model. Importantly, health professionals in remote community were more likely to feel that their access to clinical support during emergencies was consistent and immediately available. Discussion: Respondents consistently perceived the new MRaCC/ROCC model more favourably than the previous RMP‐led model, suggesting that there are benefits to having separate referral streams for telehealth advice for primary health care and emergencies, and staffing the emergency stream with specialists with advanced critical care skills. Conclusion: Given the paucity of literature about optimal models for providing pre‐hospital medical care to remote residents, the findings have substantial local, national and international relevance and implications, particularly in similar geographically large countries, with low population density.